Pola Peresepan Penggunaan Obat Demam Tifoid di Instalasi Rawat Inap RS Bhineka Bakti Husada - Neneng Sri Purwaningsih; Alfian Nita (STIKes Kharisma Persada, 2019)
Typhoid fever is an infectious disease caused by Salmonella typhi bacteria. Until now typhoid fever is still a health problem in tropical countries including Indonesia. Antibiotics are the main drugs used to treat typhoid fever. This research was conducted with observational and descriptive methods by taking data retrospectively, which means looking back at the data by looking at the medical record data for the January-December 2018 period. Sampling used a total sampling of 69 patients in the inpatient installation at Bhineka Hospital. Bakti Husada. The results showed that prescribing typhoid fever drugs at Bhineka Hospital were antibiotics and antipyretics as many as 69 cases (100%), the age of typhoid fever patients was 2-12 years old as many as 46 people (66.66%), and for the sex of the patient Typhoid fever is male as many as 41 people (59.43%). The drugs most often prescribed for typhoid fever patients are cephalosporins in the form of Ceftriaxone injection (91.30%) and antypyretics is a tablets of Paracetemol and syrup (100%).